2017
DOI: 10.1097/psy.0000000000000493
|View full text |Cite
|
Sign up to set email alerts
|

Brain Structure and Response to Emotional Stimuli as Related to Gut Microbial Profiles in Healthy Women

Abstract: Objective Brain-gut-microbiota interactions may play an important role in human health and behavior. However, while rodent models have demonstrated effects of the gut microbiota on emotional, nociceptive and social behaviors, there is little translational human evidence to date. In this study we identify brain and behavioral characteristics of healthy women clustered by gut microbiota profiles. Methods Forty women supplied fecal samples for 16s rRNA profiling. Microbial clusters were identified using Partiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
130
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 149 publications
(137 citation statements)
references
References 66 publications
7
130
0
Order By: Relevance
“…[90] In addition, the composition of the microbiota is associated with differences in affective responses to unpleasant emotional images in healthy females. [95] Supporting these correlational studies, fecal microbiota transfer of samples from depressed individuals has been shown to alter the behavioral profile of recipient microbiota-deficient mice and rats, increasing anxiety-and depression-like behaviors. [90,96] Finally, different probiotic strains have been shown to reduce symptoms of anxiety and depression across several studies in clinical and healthy populations.…”
Section: Anxiety-and Depression-like Behavior Are Regulated By Gut MImentioning
confidence: 88%
See 3 more Smart Citations
“…[90] In addition, the composition of the microbiota is associated with differences in affective responses to unpleasant emotional images in healthy females. [95] Supporting these correlational studies, fecal microbiota transfer of samples from depressed individuals has been shown to alter the behavioral profile of recipient microbiota-deficient mice and rats, increasing anxiety-and depression-like behaviors. [90,96] Finally, different probiotic strains have been shown to reduce symptoms of anxiety and depression across several studies in clinical and healthy populations.…”
Section: Anxiety-and Depression-like Behavior Are Regulated By Gut MImentioning
confidence: 88%
“…Although two studies failed to find a relationship between overall microbiota composition and amygdala volume in IBS patients and healthy women, [95,123] another identified a particular bacterial phylum that was associated with microstructure of this region. [128] That is, abundance of Actinobacteria correlated with increased fractional anisotropy in the amygdala.…”
Section: Amygdala Morphology and Gut Microbiotamentioning
confidence: 99%
See 2 more Smart Citations
“…Metagenomics techniques can, in a single run, characterize the genetic material of the host and also of every pathogen present in the sample at the moment of death. Both advantages would be useful for canopic jar analysis, potentially relating organs from the same individual, thanks to genetic profiling, but also in order to screen genetic disorders and pathogens, and even more ambitiously, reconstruct whole microbial communities that live in our body, or microbiome, known to be intimately related with abdomen, neural, inflammatory and immune conditions [66][67][68][69]. Some applied examples: in a confirmation study performed by Shin et al [70] on a 17th century AD Korean Mummy diagnosed with atherosclerotic cardiovascular disease, several risk alleles related with the condition were found, indicating genetic predisposition of the disease.…”
Section: Discussionmentioning
confidence: 99%